Regulating osteogenesis and adipogenesis in adipose‐derived stem cells by controlling underlying substrate stiffness. Issue 4 (10th November 2017) - Zhang, Tao; Lin, Shiyu; Shao, Xiaoru; Shi, Sirong; Zhang, Qi; Xue, Changyue; Lin, Yunfeng; Zhu, Bofeng; Cai, Xiaoxiao
Abstract : Cells reside in a complex microenvironment (niche) in which the biochemical and biophysical properties of the extracellular matrix profoundly affect cell behavior. Extracellular stiffness, one important bio‐mechanical characteristic of the cell niche, is important in regulating cell proliferation, migration, and lineage specification. However, the mechanism by which mechanical signals guide osteogenic and adipogenic commitment of stem cells remains difficult to dissect. To explore this question, we generated a range of polydimethylsiloxane‐based matrices with differing degrees of stiffness that mimicked the stiffness seen in natural tissues and examined adipose stem cell morphology, spreading, vinculin expression, and differentiation along the osteogenic and adipogenic pathways. Rigid matrices allowed broader cell spreading, faster growth rate and stronger expression of vinculin in adipose‐derived stem cells. In the presence of inductive culture media, stiffness‐dependent osteogenesis and adipogenesis of the adipose stem cells indicated that there was a combinatorial effect of biophysical and biochemical cues; no such lineage specification was observed in normal media. Osteogenic differentiation behavior showed a correlation with matrix rigidity, as well as with elevated expression of RhoA, ROCK‐1/‐2, and related proteins in the Wnt/β‐catenin pathway. The result provides a comprehensive understanding of how stem cells respond to the surrounding microenvironment and points to the fact that matrix stiffness is a critical element in biomaterial design and this will be an important advance in stem cell‐based tissue engineering. Abstract : Substrate stiffness is a potent regulator in osteogenic and adipogenic differentiation of adipose‐derived stem cells. Our result provides a comprehensive understanding of how stem cells respond to surrounding microenvironment and points to the fact that matrix stiffness is a critical element in biomaterial design.